Identifying animal welfare impacts of livestock air transport. Issue 5 (9th March 2020) - Collins, T; Stockman, C; Hampton, JO; Barnes, A
Abstract : Air transport of livestock occurs frequently from most Australian major cities. The total journey time starts with road transport from the farm or pre‐export facility to the departing airport where livestock are crated, and ends with the unloading of animals at the premises or farm in the importing country. We reviewed the literature regarding airfreight and conclude that there was minimal information on current practices within this industry, particularly for procedures after arrival at the Australian airport, and during the on‐board phase.